Peningkatan Kemampuan Teknologi Pembelajaran Berbasis Entertainment Melalui Pemanfaatan Gamifikasi Bagi Siswa SMA - Anggraini, Putri; Renita Astri; Mulya, Dio Prima; ., Zulfahmi; ., Faradika; ., Sularno; Kamal, Ahmad; Utnasari, Intan (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
The orientation of learning and education in the 21st century in the era of the industrial revolution 4.0 refers to the realization of 21st century life skills. The 21st Century Skills/Competencies/Skills are: 1).Creativity, namely new ideas, concepts, or products that meet the needs of the world. 2) Critical Thinking and Problem Solving, the ability to design and manage projects, solve problems, and make effective decisions using a variety of tools and resources. 3) Communication. not only for the ability to communicate effectively, orally and in writing, and with various digital tools, but also listening skills, and 4) Collaboration. As educators at Dharma Andalas University, one of the Community Service (PKM) lecturer groups consisting of 3 (three) lecturers of the Information Systems study program held Gamification training activities for students of SMAN 1 and SMAN 2 Solok City. This training aims to enable students to build game applications that can avoid boredom and foster their focus and interest in teaching materials using the QuickApp Ninja application. The application that is built is expected to produce works in the form of student creativity that supports the learning process so that this PKM activity becomes one of Dharma Andalas University's efforts to help students to improve their performance in tests and academic assignments.